If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Ax + 4y + 4x + ay = 0 Reorder the terms: ay + 4x + xA + 4y = 0 Solving ay + 4x + xA + 4y = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4x' to each side of the equation. ay + 4x + xA + -4x + 4y = 0 + -4x Reorder the terms: ay + 4x + -4x + xA + 4y = 0 + -4x Combine like terms: 4x + -4x = 0 ay + 0 + xA + 4y = 0 + -4x ay + xA + 4y = 0 + -4x Remove the zero: ay + xA + 4y = -4x Add '-1xA' to each side of the equation. ay + xA + -1xA + 4y = -4x + -1xA Combine like terms: xA + -1xA = 0 ay + 0 + 4y = -4x + -1xA ay + 4y = -4x + -1xA Add '-4y' to each side of the equation. ay + 4y + -4y = -4x + -1xA + -4y Combine like terms: 4y + -4y = 0 ay + 0 = -4x + -1xA + -4y ay = -4x + -1xA + -4y Divide each side by 'y'. a = -4xy-1 + -1xy-1A + -4 Simplifying a = -4xy-1 + -1xy-1A + -4 Reorder the terms: a = -4 + -4xy-1 + -1xy-1A
| x=1.04*y+6.18 | | 2x+3y+1z=51.4 | | X^3/3=65 | | X/3=65 | | 6(y-5)=4(y+2) | | 5y=10x+2 | | x*2-8=8 | | 5n+4=2n+33 | | 3(a+7)=36 | | a^5+4=15 | | C/3C | | 4x-11=46 | | 3x+5=-8x-4 | | 4t-9=0 | | 7m+5=55 | | 1.74x+x=.1 | | 6h-3=15 | | 3g+6=15 | | x/3+x/12=15/4 | | 4/x=5/-6 | | 3n^2+6n-13=0 | | R=ir | | (2x-3)*(2x-3)=25 | | 6+6x=4x-10 | | Y=(x-2)(x+3) | | 4sint+3cost=0 | | 3x+30=2x-10 | | Y=(x+4)(x+1) | | Y=(x+4)(c+1) | | 12w=14 | | w/4=7.2 | | -7x+5=1-3x |